Nonalcoholic Fatty Liver Disease - An Update 2019
DOI: 10.5772/intechopen.81297
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Therapy and Autoimmune Disease with Relevance to Non Alchoholic Fatty Liver Disease

Abstract: The diabetes epidemic is now expected by the year 2050 to become a global pandemic with approx. 592 million affected in both the developed and developing world. The treatment of diabetes by insulin therapy has been the focus for many diabetics with the improvement and prevention of various diseases such as cardiovascular disease, kidney disease and neurodegeneration. The global nonalcoholic fatty liver disease (NAFLD) epidemic has now become of major concern to diabetes with critical interest in insulin therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Plasma sirtuin 1 levels have been shown to be reduced in NAFLD, obesity, diabetes and other chronic diseases. Aerobic and resistance exercise that maintain metabolic control is possibly linked to activation of Sirtuin 1 and the reversal of liver steatosis/early NAFLD [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma sirtuin 1 levels have been shown to be reduced in NAFLD, obesity, diabetes and other chronic diseases. Aerobic and resistance exercise that maintain metabolic control is possibly linked to activation of Sirtuin 1 and the reversal of liver steatosis/early NAFLD [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The peptide apelin and its receptor APJ (G protein-coupled receptor) play an important role in various tissues and the role in stress, insulin resistance, hormone release, thermoregulation, food intake and water balance are critical to endocrinology and diabetes (Figure 1). Recent studies have indicated that apelin is now identified as an anti-aging factor and its inactivation leads to a decline in the apelinergic axis [2] with accelerated aging and programmed cell death that is linked to endocrinology, diabetes and neurodegenerative disease with relevance to the global chronic disease epidemic [3][4][5][6]. Apelin regulates the aging process by interactions with sirtuins [3] and its regulation of sirtuins 1-7 is critical in the prevention of the accelerated aging process and chronic disease.…”
Section: Editorialmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a metabolic malfunction, characterized by a prolonged high blood glucose level, the prevalence of which has been steadily elevating in the past decades ( Martins, 2014 ; Zhang et al, 2020 ). DM occurs when the pancreas produces insufficient insulin, and/or the body tissues, such as the liver, resist the actions of insulin ( Martins, 2018a ). Animal models, as in the studies on many other human diseases, have been wildly applied to the investigations of this metabolic disorder affecting multiple organ systems ( Martins, 2017 ; Kleinert et al, 2018 ; Backman et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%